Relationship of serum uric acid and Killip class on mortality after acute ST-segment elevation myocardial infarction and primary percutaneous coronary intervention. (1st January 2017) - Liu, Cheng-Wei; Liao, Pen-Chih; Chen, Kuo-Chin; Chiu, Yu-Wei; Liu, Yuan-Hung; Ke, Shin-Rong; Wu, Yen-Wen
Abstract: Background: There is conflicting information regarding the association between hyperuricemia and survival in STEMI patients. Our study examined the interaction between hyperuricemia and Killip class on mortality of STEMI patients. Methods: We analyzed 951 consecutive STEMI patients between February 2006 and September 2012. Hyperuricemia was defined as SUA of at least 7 mg/dL in males and 6 mg/dL in females. Killip class I patients were divided into hyperuricemia and normouricemia groups. Results: The Killip class I hyperuricemia and normouricemia groups had similar baseline and procedural characteristics, but the hyperuricemia group had significantly greater BMI, serum creatinine, and SUA, and a lower TIMI risk score (2, IQR: 1–4 vs. 3, IQR: 2–4, p = 0.019). The hyperuricemia group also had greater 30-day and 1-year mortality rates (2.9% vs. 0.3%, p = 0.022; 6.5% vs. 1.1%, p = 0.002, respectively). However, hyperuricemia was not associated with mortality of patients in Killip classes II–IV or in the overall study population. Hyperuricemia was associated with increased mortality in subgroups of patients who were at least 65 years-old, male, had BMI of 25 kg/m 2 or less, were in Killip class I, without diabetes, and who did not receive intra-aortic balloon pump support. Hyperuricemia interacted with Killip class I in increasing the risk for 1-year mortality ( p for interaction = 0.038). Conclusions: Hyperuricemia increased the 1-year mortality of STEMI patients in Killip class I, but not of patients in Killip classes II–IV. An interaction of hyperuricemia and Killip class significantly affects the mortality of STEMI patients. Highlights: Elevated SUA is associated with increased mortality in STEMI patients. Hyperuricemia and Killip class that interact with each other are associated with mortality. Hyperuricemia is significantly associated with higher mortality in STEMI patients with Killip I, but not in those with Killip II-IV.